Pengaruh Pemilihan Lokasi Usaha Terhadap Pendapatan Usaha Mikro Kedai Kopi di Kecamatan Kebon Jeruk - Ninda Ainin Alifio; Hardi, Ode Sofyan; Hijrawady, Sony Nugratama (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2024)
The purpose of this study is to find out "How do business location selection factors affect coffee shop micro businesses in Kebon Jeruk District". The methodology used in this study is a quantitative research with a causal associative research design that seeks relationships between two or more variables. Likewise, in this study, we are looking for a relationship between independent variables and bound variables. The data collection technique in this study was carried out through literature studies, documentation and questionnaires aimed at 35 (thirty-five) coffee shop micro business managers in Kebon Jeruk District. The analysis technique used in this study is multiple regression analysis which is useful to test the strength of the relationship between independent variables (variable X); accessibility (X1), visibility (X2), business environment (X3), business land (X4) with bound variables (Y); coffee shop micro business income (Y). The results of the study show that of the 5 (five) variables of location selection factors, there are three factors that have a partial influence on income, namely accessibility variables, business environment and competition. Then that all independent variables, namely accessibility, visibility, business environment, competition, and business land have a significant effect simultaneously (together) on the income of coffee shop micro businesses in Kebon Jeruk District.